2020
DOI: 10.1520/mpc20190081
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Processing Maps for Hot Deformation of Modified AISI 321 Austenitic Stainless Steel

Abstract: Hot deformation studies and optimization of hot working parameters and corresponding microstructure evolution were explored in a modified AISI 321 austenitic stainless steel. Hot compression tests were carried out in the temperature range of 800°C–1,100°C and five different strain rates (0.001–10 s−1). Processing maps were developed based on the results of hot compression tests, employing the principles of dynamic materials model and various domains of microstructure evolution were identified. The stable and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Ghazani et al [27] indicated that the critical damage value increases with the increase of deformation temperature and decrease of strain rate, and the lower the critical damage value, the higher is the risk of plastic fracture. The processing windows with the lowest fracture risk for 321 stainless steel are 0.001 s −1 , 1025-1075 • C, and 1150-1200 • C. The distribution flow instability zone in literature [15] is similar to that reported in this paper, but the safe processing temperature is lower at 900-1000 • C. The coarse-grained structure may be the reason because this is more dependent on high temperature than the finegrained structure. Therefore, the safe processing window of the tested steel is 1000-1200 • C and 0.01-0.1 s −1 .…”
Section: Hot Processing Mapssupporting
confidence: 80%
See 2 more Smart Citations
“…Ghazani et al [27] indicated that the critical damage value increases with the increase of deformation temperature and decrease of strain rate, and the lower the critical damage value, the higher is the risk of plastic fracture. The processing windows with the lowest fracture risk for 321 stainless steel are 0.001 s −1 , 1025-1075 • C, and 1150-1200 • C. The distribution flow instability zone in literature [15] is similar to that reported in this paper, but the safe processing temperature is lower at 900-1000 • C. The coarse-grained structure may be the reason because this is more dependent on high temperature than the finegrained structure. Therefore, the safe processing window of the tested steel is 1000-1200 • C and 0.01-0.1 s −1 .…”
Section: Hot Processing Mapssupporting
confidence: 80%
“…Poliak et al [18] indicated that although DRX had occurred, there was no obvious peak stress on the flow curves. However, flow curves often show obvious softening for single-phase austenitic stainless steel [10,14,15]. This may be related to the existence of the δ phase because flow curves do not only reflect the work-hardening and dynamic softening behavior of single-phase austenite.…”
Section: Flow Behavior and Hot Deformation Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a particular lack of papers concerning non-commercial steel 08Ch18N10T according to GOST standards, developed especially for the needs of nuclear engineering, and which is subject to higher demands for its mechanical properties and micropurity. Some publications have also studied the deformation behavior of AISI321 steel [19][20][21][22], rolling or forging conditions and their effect on the strain hardening of 08Ch18N10T steel, or the course of solution and stabilization annealing [23]. It is known that these forming operations have a certain effect on the production process of the steel.…”
Section: Introductionmentioning
confidence: 99%